The big book of beading patterns : for peyote stitch, right angle weave, square stitch, brick stitch, herringbone, and loomwork designs (Kalmbach Books, 2010)
Patterns to make beaded bracelets, amulets, tapestries, and more, divided into chapters by topics such as animals, flowers, and holidays.